Ferrihydrite deposited on cotton textiles as protection media against the chemical warfare agent surrogate (2-chloroethyl ethyl sulfide). Issue 10 (16th February 2017) - Wallace, Rajiv; Giannakoudakis, Dimitrios A.; Florent, Marc; Karwacki, Christopher J.; Bandosz, Teresa
Abstract : An active phase of ferrihydrite was deposited on cotton using a simple dip-and-dry process. Abstract : An active phase of ferrihydrite was deposited on cotton using a simple dip-and-dry process. The iron loading was between 4 and 10%, depending on the form of cotton and the number of dip-and-dry cycles. The materials were tested for the removal of a mustard gas surrogate, 2-chloroethyl ethyl sulfide (CEES). The modified fibers showed enhanced photoreactivity and adsorption performance compared to bulk ferrihydrite. The analysis of the headspace and of the surface of the samples after exposure to CEES revealed the presence of reaction products, indicating the high chemical activity of the ferrihydrite phase. Reaction mechanisms involving sulfonium intermediates are proposed. The chemical activity is linked to the high dispersion of the inorganic phase, which increases the number of available catalytic sites and thus enhances the direct contact of these actives sites (OH terminal groups, Fe 3+, defects) with CEES.